THE RELATIONSHIP BETWEEN TRUST IN SUPERIORS AND WORK DISCIPLINE AMONG TEACHERS AT SMK N 5 AND SMK N 11 SEMARANG - Irfanto, Dzulfiqar Adi (Ridwan Institute, 2025)
The relationship between work discipline, leadership, and trust in superiors has been well documented. This study aims to investigate the relationship between trust in supervisors and work discipline among teachers at SMK Negeri 5 and 11 Semarang. A sample of 90 teachers with civil servant status was obtained through convenience sampling, which allowed for accessible and voluntary participation. The trial of the measurement tools was conducted on July 24 and 25, 2018, involving 39 teachers from both schools. The research findings demonstrate a significant positive relationship between Trust in Superiors and teachers' work discipline. Moreover, the research highlights the importance of effective leadership practices in educational settings. The findings may serve as a foundation for future research, encouraging further exploration of the factors influencing teacher behavior and the development of strategies aimed at fostering trust within educational institutions.